Is poor air quality in day‑care centres’ affecting our children’s health? A study of indoor air quality in childcare facilities located in Perth, Western Australia - Gilbey, Suzanne; Zhao, Yun; Lee, Andy; Rumchev, Krassi (Springer Nature, 2023)
Poor indoor air quality (IAQ) can adversely affect children’s health; however, limited studies have quantified indoor air pollutants in day-care centres (DCCs) where infants and young children are increasingly spending more time from a younger age. The aim of this study was to investigate seasonal IAQ in Western Australian childcare facilities at both heavy traffic and low traffic locations. In 22 centres, total volatile organic compounds, formaldehyde, nitrogen dioxide, carbon dioxide, and carbon monoxide, particulate matter (PM) measured in six size fractions (total PM, PM10, PM4, PM2.5, PM1, ultrafine particles), and meteorological parameters (temperature and relative humidity), were continuously sampled over a 24-h period, in the cold season and repeated in the warm season. All contaminants (other than formaldehyde) in the summer and/or winter collections, or averaged over both seasons, were found to be above contemporary air quality standards, guidelines, best practice statements, or other available guidelines developed to protect human health. Furthermore, all contaminants were present at higher concentrations indoors where a DCC was located within 100 m of a heavy traffic roadway. The findings of this study suggest that children who attend these facilities on a regular basis may be chronically exposed to a range of health damaging contaminants during critical stages of their development. The findings support the need for measures to reduce concentrations of air pollutants in DCCs. Preventative actions such as attention to DCC siting, selection of appropriate building materials and furnishings, improvement in ventilation, and usage of ‘green’ cleaning products should be considered to reduce children’s exposures to harmful airborne contaminants.